Experimental Learning Model Application Of Offline Learning For Class 1 Students In Mathematics Lessons In SD IT Lentera - Kamelia Kamelia; Nur Aisyah; Melisa Hasibuan; Yuli Asnita; Halimatus Sakdiah (STKIP Rokania Pasir Pangaraian, 2021)
Mathematics is generally defined as a field of sciene that studies patterns of structure of change and space, so informally it can also be referred to as the science of numbers and the pattern referred to hare is in a broad sense that includes almost all types of order that our minds can understand as a child studying mathematics by diligebtly honing his intelligence according to experts, the child is quick to understand problems, devise solutions, and solve problems logically and systematically. This research is a quantitative study that aims to improve the mathematics learning outcomes of grade 1 students at SD IT Lentera. This research is motivated by the low learning outcomes of students, on this basis the researcher applies a direct learning model to improve student mathematics learning outcomes of students, on this basic the researcher applies a direct learning model to improve student mathematics learning outcomes. The problem raised in the study is low competence. Teachers in carrying out offline learning according to standard proces during the Covid-19 outbreak, while one of teacher’s duties is to carry out meaning ful learning in order to achieve maimum learning objectives. The purpose of this research is to increase competence in carring out offline learning through guidance with the conssultation method of SD it lantera pasir pangaraian teachers in 2021 this research method is a quantitstive method using the learning for grade 1 students. Predict by class student learning outcomes there is an influence between learning models on studen learning outcomes. There is a creative learning on student learning outcomes,there is creative influence on student learning.there is no interraction between learning models.the results show that the learning outcomes of class i mathematics at SD IT Lentera which are made by means of media learning give better results than written learning.